Should the 3-year follow-up of FAME-3 trial guide clinical practice? A critical appraisal - Gomes, Walter J.; Kaul, Sanjay; De Caterina, Rafaelle; Brophy, James M.; Sádaba, J. Rafael; Almeida, Rui; Borger, Michael A.; Marin-Cuartas, Mateo; Falk, Volkmar; Myers, Patrick O. (The Journal of thoracic and cardiovascular surgery, 2025)
[Display omitted]